Coral-inhabiting Trapezia crabs forage on demersal plankton - Shmuel, Yaniv; Ziv, Yaron; Rinkevich, Baruch (Frontiers in Marine Science, 2022)
The Trapeziidae constitute a widely distributed and common family of obligatory coral-dwelling crabs on Indo-west Pacific coral reefs, feeding on coral tissue and mucus. In situ nocturnal surveys on Stylophora pistillata (a common branching pocilloporid coral species in the Gulf of Eilat, Red Sea), revealed Trapezia cymodoce and Trapezia digitalis crabs foraging on swimming demersal plankton, including amphipods, copepods, isopods, swimming polychaetes, and occasionally fishes, employing three plankton feeding mechanisms. Laboratory experiments demonstrated that crabs actively searched for Artemia when these were present in the aquaria together with either dead or live coral branches, but did not do so when corals were absent. Overall, the results indicate that trapeziid crabs play a role as planktivorous reef organisms. This suggests the need for further study of the feeding habits of members of this family, considering the potential impacts of their foraging on demersal plankton dynamics in coral reefs.